2003
DOI: 10.1002/lsm.10167
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of temperature dependent mechanical behavior of cartilage

Abstract: The anisotropic mechanical behavior of cartilage was quantitatively analyzed in the transversely and longitudinally oriented specimens. Viscoelastic behavior appeared to be strongly dependent on the water content. Using empirically determined estimates of the transition zone temperature range accompanying stress relaxation, the activation energy for stress relaxation was calculated using time and temperature superposition theory and WLF equation. Further investigation of the molecular changes, which occur duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 39 publications
(60 reference statements)
1
54
0
Order By: Relevance
“…As the temperature is increased, the denaturation of collagen occurs. During denaturation, not only the structure but also the hydration of collagen changes, and thus, not surprisingly, thermal denaturation can lead to remarkable property changes in collagenous tissues, such as the mechanical (Aksan and McGrath, 2003;Bass et al, 2004;Chae et al, 2003;Chao et al, 2001;Chen and Humphrey, 1998;Chen et al, 1997Chen et al, , 1998aDiaz et al, 2001;Harris and Humphrey, 2004;Kondo et al, 2005;Spoerl et al, 2004;Wang et al, 2005;Wells et al, 2004), thermal (Davis et al, 2000;Naseef et al, 1997;Siapi et al, 2005;Tsereteli et al, 1997), and optical (Agah et al, 1996;Bosman, 1993;Essenpreis, 1992;Jun et al, 2003;Lin et al, 1996;Pickering et al, 1994;Ritz et al, 2001a,b;Schwarzmaier et al, 1998;Thomsen and Vijverberg, 1993) properties. However, there are comparatively few studies on skin tissue (Le Lous et al, 1985;Melling et al, 2000;Pierce et al, 2004;Reihsner et al, 2000), despite the skin's dermis being mainly composed of collagen.…”
Section: Discussionmentioning
confidence: 95%
“…As the temperature is increased, the denaturation of collagen occurs. During denaturation, not only the structure but also the hydration of collagen changes, and thus, not surprisingly, thermal denaturation can lead to remarkable property changes in collagenous tissues, such as the mechanical (Aksan and McGrath, 2003;Bass et al, 2004;Chae et al, 2003;Chao et al, 2001;Chen and Humphrey, 1998;Chen et al, 1997Chen et al, , 1998aDiaz et al, 2001;Harris and Humphrey, 2004;Kondo et al, 2005;Spoerl et al, 2004;Wang et al, 2005;Wells et al, 2004), thermal (Davis et al, 2000;Naseef et al, 1997;Siapi et al, 2005;Tsereteli et al, 1997), and optical (Agah et al, 1996;Bosman, 1993;Essenpreis, 1992;Jun et al, 2003;Lin et al, 1996;Pickering et al, 1994;Ritz et al, 2001a,b;Schwarzmaier et al, 1998;Thomsen and Vijverberg, 1993) properties. However, there are comparatively few studies on skin tissue (Le Lous et al, 1985;Melling et al, 2000;Pierce et al, 2004;Reihsner et al, 2000), despite the skin's dermis being mainly composed of collagen.…”
Section: Discussionmentioning
confidence: 95%
“…Instead, these findings suggest that in order to produce clinically relevant shape change in cartilage tissue using the Nd:YAG, significant cellular damage will occur within the region of energy deposition and heat conduction [2]. The success of LCR procedures reported in both animal studies [2,12] and clinical trials [11] likely depends upon spatially selective heating where reshaping may result from deposition of energy into well-defined layers within a specimen or graft leading to mechanical relaxation of this region alone [8]. Cartilage tissue beneath this level likely undergoes little temperature elevation and thus remains viable and may participate in the remodeling process.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study performed by Diaz et al clearly indicated that within this temperature range, chondrocyte viability was compromised [22]. Similarly, Chae et al showed that the temperature region associated with cartilage relaxation was in fact lower, between 50 and 658C [23].…”
Section: Discussionmentioning
confidence: 99%